A grounded theory of Filipino nurses' role performance in U.S. hospitals - Lin, Li-Chen (Ann Arbor Michigan ProQuest LLC, 2009)
In response to the nursing shortages, hospitals in the U.S. have been filling nursing positions by hiring foreign nurse graduates (FNGs). Filipino nurses represent the majority of all FNGs recruited to work in the U.S. Although Filipino nurses are not new to U.S. hospitals, very few studies have detailed how Filipino nurses have adjusted to U.S. nursing practice. The purpose of this study was to explore how Filipino nurses' perceived their role performance in the U.S. Using grounded theory as the methodology and symbolic interactionism as the philosophical underpinning, the principal investigator (PI) developed a substantive theory using a constant comparative method as the analytical approach. The PI used convenience and theoretical sampling to recruit 31 English-speaking female Filipino RNs practicing in Texas. One interview was conducted with each participant and the data were transcribed verbatim. The PI followed Strauss and Corbin's analytic steps to examine all cases, and the rigor of the theory was safeguarded by following the criteria of evaluation. All participants experienced challenges while adjusting to the U.S. healthcare system and American society due to differences in cultural expectations and experiences. The theory explains the processes of Filipino nurses' transition to U.S. nursing practice. The core variable was "transitioning from Filipino to U.S. nursing practice," which was shaped by nine relational categories. Based on descriptions from these Filipino nurses, it was clear that role transitioning from the Philippines to the U.S. is a complex phenomenon influenced by the meanings and expectations derived from these nurses' prior context in the Philippines. This theory should be beneficial to the many entities involved with or invested in Filipino nurses' migration by providing knowledge about their role transitioning. However, these findings cannot be applied to all Filipino nurses. Future research studies are needed to expand the scope of this theory and to empirically test it. Filipino nurses perceived that unethical actions were constantly taking place, regardless of existing rules and regulations. However, these nurses did little to correct or address the problems or ethical lapses themselves. Advocacy efforts are needed to ensure full understanding of immigration laws and policies to ensure fair work practices for Filipino nurses working in the U.S.--Abstract.
Thesis (Ph.D.)--University of Texas at Austin, 2009.
Keywords: Nurses -- Philippines; Nurses, Foreign -- United States; Transcultural nursing